57.9k views
3 votes
How do you write y+1=4/5(x-3) in standard form?

1 Answer

4 votes

Answer:

The standard form of the given expression is
- ((4)/(5))x + y +  ((17)/(5))   = 0

Explanation:

Here, the given expression is
y + 1 = (4)/(5)  (x-3)

Now, the Standard Form of the equation is ax + by + c = 0

Solving this, we get:


y + 1 = (4)/(5)  (x-3)  \implies y + 1 = ((4)/(5))x  - (12)/(5)


y + 1   - ((4)/(5))x + ((12)/(5))  = 0

or,
y  - ((4)/(5))x + ((12)/(5)  + 1 )= 0  \implies y  - ((4)/(5))x + ((12+ 5)/(5))   = 0


y  - ((4)/(5))x + ((17)/(5))   = 0

Hence, the standard form of the given expression is
- ((4)/(5))x + y + ((17)/(5))   = 0

User Gerrie Schenck
by
5.4k points